2009
DOI: 10.1002/lary.20723
|View full text |Cite
|
Sign up to set email alerts
|

Membranous labyrinth volumes in normal ears and Ménière disease: A three‐dimensional reconstruction study

Abstract: Objectives The purpose of this study was to determine the normal volume ranges of cochlear duct, saccule, and utricle, and to assess endolymphatic hydrops in Ménière disease. Study Design Retrospective temporal bone study. Methods Three-dimensional (3-D) images of membranous labyrinth were reconstructed from 31 normal temporal bones, six temporal bones from three patients with bilateral Ménière disease, and 16 temporal bones from eight patients with unilateral Ménière disease. Volumes of each part of membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 13 publications
5
22
0
1
Order By: Relevance
“…In the present study, significant EH was observed in either the cochlea or vestibule in three of four asymptomatic ears in patients with unilateral MD. These MRI findings are consistent with histopathology findings of the temporal bone showing that the contralateral ears of patients with unilateral MD occasionally develop asymptomatic EH [17,18]. We experienced one patient with barotrauma in whom Gd enhancement was observed in the fundus of the internal auditory meatus.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, significant EH was observed in either the cochlea or vestibule in three of four asymptomatic ears in patients with unilateral MD. These MRI findings are consistent with histopathology findings of the temporal bone showing that the contralateral ears of patients with unilateral MD occasionally develop asymptomatic EH [17,18]. We experienced one patient with barotrauma in whom Gd enhancement was observed in the fundus of the internal auditory meatus.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with previous studies about experimental EH and MD [21,22]. In the current study, the volume of the utricle was also increased, but that of the lateral canal ampulla did not change.…”
Section: Discussionsupporting
confidence: 83%
“…To demonstrate that the reduced perilymphatic enhancement is caused by EH, it could be useful to verify whether medical or surgical treatment known to influence hydrops may modify imaging outcomes. Interestingly, anecdotal descriptions have recently been reported on cases of patients with atypical or definite MD, showing improvement both in hearing threshold and inner ear enhancement in MRI, after medical treatment (21,27).…”
Section: Discussionmentioning
confidence: 98%